Characterization of a hotspot for mimicry: assembly of a butterfly wing transcriptome to genomic sequence at the HmYb/Sb locus - LAURA FERGUSON; SIU FAI LEE; NICOLA CHAMBERLAIN; NICOLA NADEAU; MATHIEU JORON; SIMON BAXTER; PAUL WILKINSON; ALEXIE PAPANICOLAOU; SUJAI KUMAR; THUAN‐JIN KEE; RICHARD CLARK; CLAIRE DAVIDSON; et al. (Molecular Ecology, 2010)
The mimetic wing patterns of Heliconius butterflies are an excellent example of both adaptive radiation and convergent evolution. Alleles at the HmYb and HmSb loci control the presence/absence of hindwing bar and hindwing margin phenotypes respectively between divergent races of Heliconius melpomene , and also between sister species. Here, we used fine‐scale linkage mapping to identify and sequence a BAC tilepath across the HmYb/Sb loci. We also generated transcriptome sequence data for two wing pattern forms of H. melpomene that differed in HmYb/Sb alleles using 454 sequencing technology. Custom scripts were used to process the sequence traces and generate transcriptome assemblies. Genomic sequence for the HmYb/Sb candidate region was annotated both using the MAKER pipeline and manually using transcriptome sequence reads. In total, 28 genes were identified in the HmYb/Sb candidate region, six of which have alternative splice forms. None of these are orthologues of genes previously identified as being expressed in butterfly wing pattern development, implying previously undescribed molecular mechanisms of pattern determination on Heliconius wings. The use of next‐generation sequencing has therefore facilitated DNA annotation of a poorly characterized genome, and generated hypotheses regarding the identity of wing pattern at the HmYb/Sb loci.